TEACHERS’ CREATIVITY PROMOTION WITH RESPECT TO TEACHING EXPERIENCE, TEACHING LEVEL, SECTOR AND GENDER VISE SCHOOLING SYSTEM, AND SUBJECT TEACHERS TEACH: EVIDENCE FROM A BROADER PAKISTANI CONTEXT - Kamran, Muhammad (Journal of Peace, Development and Communication, 2022)
This research article drove us to inspect the perception of Pakistani teachers’ creativity promotion with respect to teaching experience, teaching level, sector and gender vise schooling system, and subject teachers teach in their classrooms. We used the quantitative research design and applied the survey (questionnaire) as a method of data collection to achieve objectives. Our population of interest was composed of multilevel teachers from broader perspective in Pakistan who taught at various levels and were teaching different subjects in different schooling systems. For data collection, an online questionnaire of 11 items adapted from Sarsani (1999) sent to respondents through WhatsApp, Emails, and Facebook messenger, which responded online by 468 teachers randomly. These respondents were randomly selected through a simple random sampling method. Of 468 questionnaires, one questionnaire was rejected due to missing options, so it made our total sample 467 teachers. The results revealed that Pakistani teachers perceived that creativity among the students must be promoted. About creativity promotion, when the Pakistani teachers’ perception was tested against the teaching experience, teaching level, schooling system (sector vise & gender vise) and subjects they teach, significant differences were found only in teaching experience and teaching at different levels. The rest of the demographic variables i.e., schooling system (sector vise & gender vise) and subjects they teach did not yield any significant differences. The results extracted from current study were discussed in light of the past studies on the basis of which recommendations were given.